Pengaruh Dihedral Bow Variasi Three Master Curves Terhadap Hambatan Total Kapal Ikan Menggunakan Metode Cfd - Alfian Andhika Putra (Fakultas Teknik, 2026)
This study investigates the effect of dihedral bow variations using Three Master Curves on the total resistance of a traditional fishing vessel through Computational Fluid Dynamics (CFD). Sixteen dihedral bow models were developed by varying the K-curve angle (105°, 110°, 115°, and 120°) and the C curve height (100%, 115%, 85%, and 70%). Simulations were conducted at speeds of 10, 12, and 15 knots. The results show that the application of dihedral bow significantly affects the hydrodynamic performance and total resistance of the vessel. The lowest resistance at 15 knots was obtained by Model 6 with a K-curve angle of 110° and a C-curve height of 115%, producing a resistance value of 923.354 N and reducing resistance by approximately 47.9% compared to the model 1 hull. Meanwhile, the highest resistance was produced by Model 16 with a resistance value of 1818.95 N. Based on the average resistance values at all testing speeds, Model 1 with a K-curve angle of 105° and a C-curve height of 100% showed the most optimal overall performance, with the lowest average resistance value of 782.37 N. The results indicate that an appropriate combination of Three Master Curves can improve flow distribution and reduce wave-making resistance on traditional fishing vessels.
Validasi dan Finalisasi Ratna 23 Juli 2026
Keywords: Hambatan Kapal; CFD; Kapal Ikan; Computational Fluid Dynamics; Dihedral Bow